Canada : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
After recovering rapidly from the Great Recession, the Canadian economy has slowed down in 2012. Growth weakened in the first three quarters of 2012, and recent indicators have suggested that the pace of economic expansion remained subpar in the fourth quarter. The fiscal policy has continued to be a drag on growth, as the stimulus is being withdrawn. These have been only partly offset by an improvement in financial conditions in 2012. Growth is expected to gain new momentum over 2013.